O przezwiskach gimnazjalistów kaliskich (analiza semantyczna) - Lewicka, Marta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The article presents the semantic analysis of students’ nicknames. The onomastic material has been taken from a sample survey conducted in one of secondary school in Kalisz at a school year 2013/2014. The material basis consists of 269 personal names. The anthroponyms formed on common names are analysed in detail in the article. The main aim of the study is to observe the connections between the nicknames and the common names which motivate them. The semantic analysis and the statistical analysis of school nicknames allow to notice and reconstruct the mechanisms which affect nicknames formation as well as to observe the connections between the name and the designatum.